2022
DOI: 10.5829/ije.2022.35.04a.07
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Examination of Gas-liquid Two-phase Flow Patterns in an Inclined Rectangular Channel with 90° Bend for Various Vertical Lengths

Abstract: In order to realize the behavior of two-phase flow in an inclined rectangular channel with 90̊ bend for various vertical lengths, an experimental investigation has performed. The test section (a chanel with 30 m length) contains two horizontal parts and a middle vertical section. Three vertical lengths of 50, 100 and 150 cm were utilized along the test section. The cross section of the rectangular channel is 10 cm × 15 cm. Air and water were the fluids used in this work. Various flow patterns are created by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Through the dominant flow patterns that are observed in Looking at Figure 6, it could be concluded that after a certain value of the air velocity the void fraction curves face an almost constant slope. It should be noted that the above-mentioned statement is in good agreement with previously presented findings of some other investigations, from which their work were published by Jiang and Rezkallah [25], Usui and Sato [26], Nguyen [27] and Vatani and Domiri-Ganji [28] could be named.…”
Section: Resultssupporting
confidence: 91%
“…Through the dominant flow patterns that are observed in Looking at Figure 6, it could be concluded that after a certain value of the air velocity the void fraction curves face an almost constant slope. It should be noted that the above-mentioned statement is in good agreement with previously presented findings of some other investigations, from which their work were published by Jiang and Rezkallah [25], Usui and Sato [26], Nguyen [27] and Vatani and Domiri-Ganji [28] could be named.…”
Section: Resultssupporting
confidence: 91%
“…According to laboratory experiments, a high pressure drop leads to selective production of sand particles with diameters of 1 -20 μm and 40 -200 μm. Literature analysis (61,62) has shown that particles with a diameter of less than 50 μm do not create sand plugs, since they are carried out of the wellbore even at low rates, but have a significant effect on skin factor of the screen.…”
Section: Development Of a Combined Methods For Limiting Sand Producti...mentioning
confidence: 99%
“…In recent study, Jalili et al (26) examined the flow of a viscous fluid between porous disks under a magnetic field, comparing Akbari-Ganji Method (AGM) and the Finite Element Method (FEM). Valuable research has been conducted in the fields of microchannels, nanofluids, and heat transfer, which are reportd in literature (27)(28)(29)(30)(31)(32) and can be beneficial for future studies.…”
Section: Introductionmentioning
confidence: 99%